La incidencia del capital humano en la eficacia de los proyectos Procompite de la Municipalidad Provincial de Sánchez Carrión - período 2012-2013 - Cruz Alonzo, Feresminda Nancy (2016)
This research aims to determine the impact of human capital on the effectiveness of the PROCOMPITE projects of the municipality of Sánchez Carrión - period 2012-2013 12 beneficiaries of three projects were surveyed for the purpose of evaluating human capital in the same way the effectiveness evaluation was carried out. The results were analyzed statistically. From the study carried out, it is concluded that "Human Capital Management has a significant impact on the effectiveness of the PROCOMPITE projects of the Provincial Municipality of Sánchez Carrión"; as shown by the results of the study variables in a consolidated manner (Fig. 3.10 and 3.11), and after having estimated a numerical indicator for each variable (Fig. 3.12 and 3.13), has allowed us to appreciate the degree of closeness or relationship between both variables, since this difference is 0.7 (the acceptable maximum being 10 points, according to the margin of error considered for this research). According to a logical analysis there is a direct incidence. It is also worth mentioning that this work serves as a background for future research.